Alliances motive and the stock market response: A comparative analysis across industries - Manish Tewari; Pradipkumar Ramanlal; Rajesh Kumar; Soumendra De (Cogent Business & Management, 2019)
We analyze the announcement-period returns of 4315 two-party, non-equity alliances undertaken by US-based firms between 1986 and 2015 in 11 industries and find positive returns for all of the 11 samples, with the Drug industry reporting the highest (2.69%) cumulative abnormal return (CARs) and Wholesale Trade for Non-Durable Goods industry the lowest (0.84%) around the five-day window surrounding the announcement of the alliances. Using proxy variables, we study whether the alliances in the specific industry are motivated by Exploration, Exploitation, or a combination of both Exploration and Exploitation motive. We find strong evidence that the alliances in the Business Services; Computer and Office Equipment; Electronic and Electrical Equipment; and Telecommunications industries are Exploration motivated. Alliances in the Investment & Commodity Firms, Dealers, and Exchanges; Measuring, Medical, Photo Equipment and Clocks; Prepackaged Software; and Wholesale Trade-Durable Goods industries are motivated by the Exploitation motive, whereas alliances in the Communications Equipment and Drugs industries are motivated by both Exploration and Exploitation (dual) motives. The average CAR (ACAR) for alliances in industries motivated by both Exploration and Exploitation motives is the highest at 2.2%-thereby, creating the most value-followed by Exploitation motivated at 1.58% and Exploration motivated at 1.23%.
Keywords: D34; D74; D78; G34; L22; 650; strategic alliance; performance; exploration; exploitation; inter-industry studies